The Training of Developmental Stimulation on Children with Autism Syndrome Disorder in Autism Center of Blitar City - Suprajitno, Suprajitno (STIKes Patria Husada Blitar, 2020)
Children with Autism Syndrome Disorder (ASD) have the same developmental tasks and must be stimulated from an early age. Stimulation can be performed by parents or caregivers. This community service aimed to provide parents or caregivers with the ability to stimulate the development of children with ASD. The training was conducted on 40 parents or caregivers using the Book of Autistic Children's Activity Guide at Home: A Guide for Parents (Buku Bina Aktivitas Anak Autis di Rumah: Panduan Bagi Orang Tua) ISBN: 978-602-6397-32-4. Training conducted twice by therapists in Autism Center of Blitar City. The training evaluation used a checklist consisting of 17 abilities. The changes were known from the mean increase in ability of 15.4 and the standard deviation decreased to 7.94. After the training, there was a change in the ability to perform developmental stimulation of children with ASD and parents or caregivers said they were very satisfied because they had the guidelines to be used at home